Carbon footprint of private dental clinics in Egypt: a cross-sectional study - Amira H Elwan; Maha El Tantawi; Ahmed Mahmoud Fouda (BMC Oral Health)
Abstract Background Climate change is a global challenge, caused by increasing greenhouse gas (GHG) emissions. Dental clinical practice contributes to these emissions through patient and staff travel, waste, energy and water consumption and procurement. Carbon footprinting quantifies GHG emissions. This study assessed the Carbon Footprint (CFP) of private dental clinics in Egypt. Materials and methods Data were collected from private dental clinics in Alexandria and Elbeheira, in Northwestern Egypt from July to August 2024 through interview questionnaires. A CFP calculator was used to estimate carbon emissions from patient and staff travel, waste, energy and water consumption, and procurement. To determine the average CFP per clinic and per patient visit, the CFP of all clinics was averaged, both with and without considering the depreciation of dental equipment. Results Data from 27 dental clinics were collected. The average CFP of an Egyptian private dental clinic, which, per year, received 3,322 patient visits, and where 5 personnel worked 279 days was 14,426.8 kg CO2e, or 4.3 kg CO2e per patient visit. The largest contributor to the CFP was patient travel (45.6%), followed by staff travel (19.6%), energy consumption (18%), procurement (12.4%), waste (4.2%), and water consumption (0.3%). After considering the yearly depreciation of dental equipment, the CFP per clinic in a year increased by 12.2%. Conclusion Private dental clinics in Egypt produce substantial carbon emissions. Patient travel was the major contributor to the CFP. While there was a high CFP of electricity consumption, the CFP of gas was zero. The high CFP of waste was likely due to improper segregation and the lack of recycling. Country-specific CFP calculators are needed to accurately measure the carbon emissions of dental clinics in various settings. Preventing oral diseases, raising public awareness to sustainable practices, promoting walking and cycling, improving public transportation, implementing waste recycling, shifting to renewable sources of energy, and local manufacturing of dental products are important to reduce carbon emissions in dental clinics.